Promotion of Bronchopulmonary Dysplasia Progression Using Circular RNA circabcc4 via Facilitating PLA2G6 Expression by Sequestering miR-663a - Chen, Yu-fei; Feng, Dan-dan; Wu, Sheng-hua; Lu, Hong-yan; Banu Pasha, Asfia; Permall, Dhivya Lakshmi; Chen, Jia-he; Sun, Zhong-yi; Li, Bing-jie; Zhou, Huan; Yang, Yang; Zhang, Xiao-jie; et al. (Frontiers in Cell and Developmental Biology, 2020)
Circular RNA (circRNA) has been increasingly proven as a new type of promising therapeutic RNA molecule in a variety of human diseases. However, the role of circRNA in bronchopulmonary dysplasia (BPD) has not yet been elucidated. Here, a new circRNA circABCC4 was identified from the Agilent circRNA chip as a differentially expressed circRNA in BPD. The relationship between circABCC4 level and BPD clinicopathological characteristics and prognosis was analyzed. The function of circABCC4 was evaluated by performing CCK-8 and apoptosis analysis in vitro and BPD model analysis in vivo. RNA immunoprecipitation (RIP), luciferase reporter and rescue experiments were used to elucidate the interaction between circABCC4 and miR-663a. Luciferase reporter assay and rescue experiments were used to elucidate the interaction between PLA2G6 and miR-663a. CircABCC4 and PLA2G6 levels were increased, while miR-663a levels were decreased in the BPD group, compared to the control group. MiR-663a inhibited apoptosis by repressing PLA2G6 expression, while circABCC4 enhanced the apoptosis and inhibited the proliferation of A549 cells by sponging miR-663a and increasing PLA2G6 expression. In conclusion, circABCC4 promotes the evolving of BPD by spongening miR-663a and up-regulating PLA2G6 expression, which makes circABCC4 an ideal molecular target for early diagnosis and intervention of BPD.